The Work Ethic: What are we Mesuring? - Juzanek, Jiri (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
The author questions the traditional criteria of work ethic following profound changes in the scale of values within society.